2015
DOI: 10.1097/igc.0000000000000495
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Neuroendocrine Carcinoma of the Uterine Cervix: A Single-Institution Retrospective Review

Abstract: Radical hysterectomy followed by platinum-based chemotherapy, especially the irinotecan plus cisplatin combination, is beneficial for long-term survival in patients with early-stage neuroendocrine carcinoma of the cervix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…treatment10 mo.Median OS: 32 mo.Median DFS: 6 mo.Kuji et al (Kuji et al, 2013)/Japan201352Mixed57 mo.4-year OS & PFS:IB1: 63%, 59%IB2: 67%, 68%IIB: 30%, 13%IIIB: 29%, 17%IVB: 25%Stecklein et al (Stecklein et al, 2016)/USA201640 (NEC)Mixed21.5 mo.OS at 5-years: 27%EFS at 5-years: 20%Median OS:≤ Stage IB1: 41 mo.≥ Stage IB2: 17 mo.Lan Fang et al (Lan-Fang et al, 2012)/China201243OS at 5-years: 29%Median OS:Early stage: 89.6 mo.Late stage: 34.4 mo.Lee et al (Lee et al, 2015)/Korea2015102MixedMedian OS & TTP:Early stage: 40.7 & 22.3 mo.Late stage: 21.4 & 13.3 mo.Yuan et al (Yuan et al, 2015)/China201538 (Stage IA-IIA)Sx ± Adj. CTxOS at 5-years: 43%Median DFS: 36 mo.Nagao et al (Nagao et al, 2015)/Japan201523Mixed24 mo.5-year OS:Small cell NEC-19%Large cell NEC: 91%Li et al (Li et al, 2015a)/China201522Mixed24.1 mo.OS at 3-years: 55%DFS at 3-years: 50%3-year OS:Early stage: 68%Late stage: 0%Huang et al (Huang et al, 2014)/China201472Mixed4-year OS:IB1: 63%IB2: 67%IIB: 30%IIIB: 29%IVB:25%McCann et al (McCann et al, 2013)/USA201326Mixed27 mo.Median OS:Stage I: NRStage II-IV: 12.1 moLee et at (Lee et al, 2016)/Korea201661Sx ± Adj. Tx5-year OS:Early-42.1%, Late-23.7%Roy et al/current study25CTx + RT ± PCI54 mo.OS at 5-years: 48%PFS at 5-years: 46.4%5-year PFS & OS:Stage I-IIA: 55.7% & 62.5%Stage IIB-IVB: 0% & 22.2%Mo.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…treatment10 mo.Median OS: 32 mo.Median DFS: 6 mo.Kuji et al (Kuji et al, 2013)/Japan201352Mixed57 mo.4-year OS & PFS:IB1: 63%, 59%IB2: 67%, 68%IIB: 30%, 13%IIIB: 29%, 17%IVB: 25%Stecklein et al (Stecklein et al, 2016)/USA201640 (NEC)Mixed21.5 mo.OS at 5-years: 27%EFS at 5-years: 20%Median OS:≤ Stage IB1: 41 mo.≥ Stage IB2: 17 mo.Lan Fang et al (Lan-Fang et al, 2012)/China201243OS at 5-years: 29%Median OS:Early stage: 89.6 mo.Late stage: 34.4 mo.Lee et al (Lee et al, 2015)/Korea2015102MixedMedian OS & TTP:Early stage: 40.7 & 22.3 mo.Late stage: 21.4 & 13.3 mo.Yuan et al (Yuan et al, 2015)/China201538 (Stage IA-IIA)Sx ± Adj. CTxOS at 5-years: 43%Median DFS: 36 mo.Nagao et al (Nagao et al, 2015)/Japan201523Mixed24 mo.5-year OS:Small cell NEC-19%Large cell NEC: 91%Li et al (Li et al, 2015a)/China201522Mixed24.1 mo.OS at 3-years: 55%DFS at 3-years: 50%3-year OS:Early stage: 68%Late stage: 0%Huang et al (Huang et al, 2014)/China201472Mixed4-year OS:IB1: 63%IB2: 67%IIB: 30%IIIB: 29%IVB:25%McCann et al (McCann et al, 2013)/USA201326Mixed27 mo.Median OS:Stage I: NRStage II-IV: 12.1 moLee et at (Lee et al, 2016)/Korea201661Sx ± Adj. Tx5-year OS:Early-42.1%, Late-23.7%Roy et al/current study25CTx + RT ± PCI54 mo.OS at 5-years: 48%PFS at 5-years: 46.4%5-year PFS & OS:Stage I-IIA: 55.7% & 62.5%Stage IIB-IVB: 0% & 22.2%Mo.…”
Section: Resultsmentioning
confidence: 96%
“…A comparative description of outcome in available literature on SmCC (Boruta II et al, 2001; Zivanovic et al, 2009; Cohen et al, 2010; Kuji et al, 2013; Lee et al, 2015; Chen et al, 2008; Viswanathan et al, 2004; Wang et al, 2012a; Huang et al, 2014; Li et al, 2015a; Lee et al, 2008; Stecklein et al, 2016; Peng et al, 2012; Lan-Fang et al, 2012; Yuan et al, 2015; Nagao et al, 2015; McCann et al, 2013; Lee et al, 2016) have been summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…21 Two Japanese studies have confirmed this benefit of adjuvant chemotherapy. 22,23 Most of our patients received EP regimen as part of their treatment. This chemotherapy has shown its superiority in terms of cause specific survival in a large study by the Taiwanese Gynaecologic Oncology Group.…”
Section: Discussionmentioning
confidence: 99%
“…Etoposide/cisplatin (EP) was the most commonly used chemotherapeutic regimen for SCNCC [27]. In advanced FIGO stage, concurrent chemoradiation (CCRT) with at least five cycles of EP (CCRT-EP5+) was associated with significantly better 5-year FFS [24].…”
Section: Discussionmentioning
confidence: 99%